2014
DOI: 10.21829/myb.2014.201180
|View full text |Cite
|
Sign up to set email alerts
|

Introducción a la fotografía hemisférica en ciencias forestales

Abstract: La fotografía hemisférica es profusamente utilizada en climatología y ciencias forestales en vinculación con tecnología geomática. Permite obtener un registro detallado de los claros del dosel y estimar, tanto la estructura del mismo, como la transmisión de luz al sotobosque, ambas variables de gran importancia para el inventario forestal y el manejo de la regeneración natural. Debido a que los equipos de fotografía hemisférica tienen usos muy diversos, incluso en fotografía artística, su costo es bajo en comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Se ajustó la cámara a un trípode con el fin de asegurar o mantener estabilidad de esta. Dentro de la parcela forestal seleccionada, se colocó la cámara a una altura mayor a 1.0 m de altura sobre el nivel del suelo, para evitar interferencia de especies arbustivas o arvenses en el campo visual (Mauro-Díaz et al, 2014).…”
Section: Elaboración Propiaunclassified
“…Se ajustó la cámara a un trípode con el fin de asegurar o mantener estabilidad de esta. Dentro de la parcela forestal seleccionada, se colocó la cámara a una altura mayor a 1.0 m de altura sobre el nivel del suelo, para evitar interferencia de especies arbustivas o arvenses en el campo visual (Mauro-Díaz et al, 2014).…”
Section: Elaboración Propiaunclassified
“…This map is used to estimate the amount of direct solar radiation that a certain location in the surface model receives. The solar position (zenith and azimuth angles) is calculated as a function of latitude, day, time, and year using astronomical formulas [53]. The skymap in Figure 5 subdivides the sky vault into zenith and azimuth, grouped into different sectors.…”
Section: Solar Simulation Of the Celestial Vaultmentioning
confidence: 99%
“…The data also showed that the area reached by fire (17.65%) had a greater percentage of canopy openness when compared to the adjacent area (11.88%), thus demonstrating that fire affects the variable behavior. The highest percentage of canopy openness determines how much light penetrates inside the forest, the different levels of soil and air humidity and the direct impact of rainfall on the soil (Melo et al, 2007;Mauro-Díaz et al, 2014). Thus canopy openness modifies the microclimate in the different forest strata (Souza et al, 2014) by increasing insolation and decreasing humidity, causing the colonization by species from the seedling or soil seed banks, individuals remaining in the area, and individuals migrating from surrounding forests (Martins et al, 2008).…”
Section: Canopy Opennessmentioning
confidence: 99%